KAJIAN PENGELOLAAN BANTUAN DINAS PERTANIAN KABUPATEN MINAHASA DI DESA SENDUK KECAMATAN TOMBARIRI KABUPATEN MINAHASA (STUDI KASUS KELOMPOK TANI MASEMBORAN DAN KELOMPOK TANI BERKAT) (Agricultural Assistance Manajement Study Minahasa District in Senduk Village Kecamatan Tombariri Minahasa District (Case Study of Masemboran and Berkat Farmer Group)) - Adelia F. A. A. Rampengan; Benu Olfie L. S.; Lyndon R. J. Pangemanan (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2020)
The objective of this research is to study the planning, implementation and evaluation of assistance from the Minahasa District Agriculture Office in Senduk Village, Tombariri District, Minahasa Regency in the Masemboran and Berkat farmer groups. This research was conducted in November to May 2020. The data used in this study are primary data and secondary data. Primary data were obtained through direct interviews with Masemboran and Berkat farmer groups totaling 10 informants. Secondary data obtained from documents and other supporting data. The sampling method is done by using Purposive Sampling. Data was colleted through in-depth interviews, observation and documentation. The research result showed that all processes proceeded according to what was stated in the implementation instructions although there were some obstacles encountered, but they could be resolved. In planning, the disbursement process requires quite a long time. Exact information about the assistance that will be obtained is not yet fully available. Implementation, in making accountability reports by the management of the farmer group regarding the assistance received has experienced difficulty due to lack of recording the things needed and due to the limited time of the management to make the report. The board is open regarding information about assistance, implementation and results received.Keywords: Planning, Implementation, Evaluation, Farmer Group.